Reliability of Time-Temperature Indicator From Corn and Red Palm Oil Blending For Monitoring Microbial Growth of Pasteurized Milk - Widyasaputra, Reza; Syah, Ryan Firman; Ruswanto, Adi; Fau, Masna Yanti (Food ScienTech Journal, 2023)
Time-Temperature Indicator made from corn oil and red palm oil had a potency to be used in cold chain food system. However, the evaluation of its reliability was required. The aim of this study was to evaluate the reliability of indicator to monitor the changes of pasteurized milk quality based on microbial growth at several storage temperatures. This study was conducted in three stages. Stage 1 was making corn oil and red palm oil blending with 70:30 (%v/v) ratio. Stage 2 was measurement of diffusion length, coefficient, kinetics and activation energy at five storage temperature (4, 29, 37, 44, and 51 ºC). Stage 3 was quantification of total microbial count at three different storage temperature (8, 29, and 40 ºC). The result showed that the activation energy of corn oil and red palm oil Time-Temperature indicator was 36.796 kJ/mol. Meanwhile, the activation energy of pasteurized milk microbial growth kinetics was 44.021 kJ/mol. The reliability of indicator was good, because the activation energy difference value between microbial growth and indicator was lower than 25 kJ/mol.